Ghaws Bahar: Ormarah, 2030. The death of a language and a culture - Jahani, Carina (Orientalia Suecana, 2021)
We are pleased to present the English translation of a short story written in Balochi, together with an introduction to the life andwork of the author. We also include the text of the story in Latin and Arabic script. It is our hope that this story will never cometrue, and instead will cause those who read it to cherish their mother tongue and pass it on to future generations.